2016
DOI: 10.3390/genes8010011
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Allocation to Metabolic Pathways is Tightly Regulated and Affects the Virulence of Streptococcus mutans

Abstract: Bacteria take up and metabolize sugar as a carbohydrate source for survival. Most bacteria can utilize many sugars, including glucose, sucrose, and galactose, as well as amino sugars, such as glucosamine and N-acetylglucosamine. After entering the cytoplasm, the sugars are mainly allocated to the glycolysis pathway (energy production) and to various bacterial component biosynthesis pathways, including the cell wall, nucleic acids and amino acids. Sugars are also utilized to produce several virulence factors, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…In Streptococcus mutans, the alteration of NagB expression can affect the virulence of the bacteria [44], but the corresponding role in S. aureus remains unclear. Another protein affected by SprC is undecaprenyl diphosphate synthase, which is crucial for peptidoglycan biosynthesis and consequently influences bacterial cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…In Streptococcus mutans, the alteration of NagB expression can affect the virulence of the bacteria [44], but the corresponding role in S. aureus remains unclear. Another protein affected by SprC is undecaprenyl diphosphate synthase, which is crucial for peptidoglycan biosynthesis and consequently influences bacterial cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…The species studied included a key species for the maintenance of biofilm ecological balance that can also be present in incipient or radicular caries (A. naeslundii) and Streptococcus mutans, considered one of the most important cariogenic species [20][21][22][23][24]. The results of the present study showed that interactions between S. mutans and A. naeslundii occur during early stages of biofilm formation, leading to a decrease in lactic acid production and to a higher resistance of S. mutans to chlorhexidine exposure.…”
Section: Discussionmentioning
confidence: 62%
“…Substantial efforts have been dedicated to understanding S. mutans virulence factors [20][21][22][23] because this species is strongly associated with dental caries [24]. However, with the deeper understanding of microbial physiology within biofilms, the importance of bacterial interaction for dental biofilm cariogenicity has been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…The gene cydA encodes ubiquinone cytochrome oxidase subunit I, which is involved in bacterial electron transfer chain, and there are no studies in S.aureus that electron transfer are involved in coagulase production, although energy production genes still affect virulence factors expression [23,24] . Our studies proved that SaeRS system, ClfA, Coa and Ebh genes are essential in plasma agglutination in S.aureus [25-27] , and our research had same results.…”
Section: Discussionmentioning
confidence: 99%